DESIGN AND CONSTRUCTION OF A YOUNG COCONUT PEELING MACHINE WITH A CAPACITY OF 60 FRUITS/HOUR FOR MICRO-ENTERPRISES - Bambang; Samuel Haris Purba (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to analyze the Power motor Which needed For peeling skin coconut young ; Basics Which used For make machine peeler skin young coconut ; Calculation components construction machine peeler young coconut skin ; Time Which needed in One time peeling skin coconut young in manual ; Results Which obtained from testing tool help peeler or cutter coconut skin young. From the results of the discussion in designing the construction of a young coconut peeling machine with a capacity of 60 pieces / hour with acceptable results according to the plan. After the discussion is carried out in accordance with what is desired based on the objectives of this planning, namely: determining the motor power needed to drive the young coconut peeling machine; determining the material and size of the machine elements used; showing the work of the machine and making a working drawing of the coconut peeling machine. The results can be concluded as follows: The electric motor used = 1 hp , Belt length on the pulley = 61 inches , Motor pulley diameter = 3 inches , Pulley diameter on the coconut drive = 12 inches , Bearing = 6205 , Analysis of the cost of making the machine used Rp: 5,602,000 .